Effect of Chlorine Dioxide Fumigation on Quality and Browning of Broad Beans - ROUZHAHONG Nuerkaixi, HOU Yuanyuan, ZHAO Yaqin, ZHAO Liyan, ZHENG Yonghua, JIN Peng (Shipin Kexue, 2023)
To study the effect of chlorine dioxide fumigation on the preservation of postharvest broad beans, broad beans were fumigated with different concentrations of ClO2 (0, 15, 30 and 60 μL/L), stored at room temperature and evaluated for color difference, firmness, mass loss percentage, browning index and decay index after 0, 2, 4, 6 and 8 days. The results showed that compared to the control group, ClO2, at all concentrations tested, could inhibit the increase in mass loss percentage, browning index and decay index, and delay the decline in firmness, especially at a concentration of 30 μL/L. Furthermore, 30 μL/L ClO2 fumigation significantly reduced the respiratory intensity, inhibited chlorophyll degradation and malondialdehyde accumulation in broad beans during the 8-day storage period, suppressed the increase in superoxide anion generation rate and the accumulation of hydrogen peroxide, and maintained higher activities of superoxide dismutase (SOD) and catalase (CAT), suggesting that ClO2 fumigation could alleviate oxidative damage to the cell membrane. In addition, ClO2 treatment repressed the activities of polyphenol oxidase (PPO) and peroxidase (POD), maintained the activity of phenylalanine aminolyase (PAL) and the content of total phenols, and delayed the occurrence of browning. Moreover, ClO2 treatment increased the contents of vitamin C, soluble protein and starch, and inhibited the increase of the reducing sugar content in broad beans (P < 0.05), thus maintaining better quality of broad beans. In conclusion, 30 μL/L ClO2 fumigation effectively maintained the edible value of broad beans and improved the storage quality while enhancing the antioxidant capacity.